2021
DOI: 10.4103/ijo.ijo_117_21
|View full text |Cite
|
Sign up to set email alerts
|

Publication trend of COVID-19 and non-COVID-19 articles in the Indian Journal of Ophthalmology during the pandemic

Abstract: Purpose: To analyze the trend of COVID-19-related and non-COVID-19-related articles published in the Indian Journal of Ophthalmology (IJO) during the COVID-19 pandemic. Methods: A retrospective analysis of all COVID-19 and non-COVID-19-related articles published in all the issues of IJO from January 2020 to March 2021 was performed. The data were obtained from the official website of IJO, Editor IJO monthly email, and PubMed. The monthly data were analyzed and a compara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…These zigzag patterns showed that there was not only a figurative jump in the number of COVID-19-related submissions, but at the same time, the journal editors and reviewers made sure to publish quality research at expedited rates than normal. [ 48 ] This was the need of the time and valuable timely research publications have been instrumental in guiding ophthalmologists worldwide in restarting and making appropriate modifications in their clinics and examination approaches to deal with the pandemic safely. The highest growth rate of publications was witnessed in May 2020 with a jump of 1300% due to a sudden hike by publications of 13 articles.…”
Section: Discussionmentioning
confidence: 99%
“…These zigzag patterns showed that there was not only a figurative jump in the number of COVID-19-related submissions, but at the same time, the journal editors and reviewers made sure to publish quality research at expedited rates than normal. [ 48 ] This was the need of the time and valuable timely research publications have been instrumental in guiding ophthalmologists worldwide in restarting and making appropriate modifications in their clinics and examination approaches to deal with the pandemic safely. The highest growth rate of publications was witnessed in May 2020 with a jump of 1300% due to a sudden hike by publications of 13 articles.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the COVID-19 pandemic's impact on physical activity and studies. The increase in the number of published articles, the rapid peer review process, the rapid growth in publications, the impact factor, and the increase in citations can all be used as objective indicators of PA. During the pandemic, PA became beneficial for new and young researchers to have the desire to publish, to learn more academically, to make use of their time, and to learn research and publication in a stepby-step manner, and PA usually has the most outstanding and top-ranking authors when it comes to publications (Kaur & Gurnani, 2021;Patino & Ferreira, 2019). The physical activity research field attracts more citations as newer publications continue to expand rapidly in a short period.…”
Section: The General State Of the Scholarly Work On School-based Phys...mentioning
confidence: 99%
“…[ 1 ] Writing a manuscript, reviewing papers, publishing in a peer-reviewed journal needs skill, expertise, and background knowledge of the subject. [ 2 ] This letter is aimed at providing useful insights regarding altimetric, citation indices, citation analysis, citation indices, impact factor, and various scientific terminologies used during research and publication. We believe this will be helpful for all the authors, reviewers, and readers and may escalate the scientific output while publishing a research paper.…”
mentioning
confidence: 99%